A Quantum Resistant Chameleon Hashing and Signature Scheme. Issue 3 (4th May 2022) - Thanalakshmi, P.; Anitha, R.
Abstract : Chameleon signatures introduced by Krawczyk and Rabin are based on well-established hash-and-sign paradigm. It is a non-interactive signature scheme that simultaneously provides the properties of non-transferability and non-repudiation. The chameleon hash function is a trapdoor one-way function which prevents everyone except the holder of the trapdoor information from computing collision on a message digest. The chameleon signature scheme achieves non-transferability as the recipient of the signature is the holder of the trapdoor information. He could be able to compute collision on the hash value and hence no third party could be able to identify the real signer. In the initial constructions of chameleon signature schemes, the occurrences of collisions expose the secret key of the recipient. This strongly prevents the recipient to compute hash collisions, partially undermining the concept of non-transferability. Hence it is important to overcome this key exposure problem, and its aligned problems of key revocation and key redistribution. Also the existing chameleon signature schemes are based on the hard problems in number theory such as integer factorization or the discrete log problem over various groups. The construction of a large-scale quantum computer would render insecurity to these schemes. Hence as recommended by NISTIR 8105, we propose a quantum resistant chameleon hashing and signature scheme based on hard problems in coding theory. The scheme also satisfies the security properties of chameleon signature, such as collision resistance, semantic security, key exposure freeness, non-transferability and unforgeability. As code-based cryptosystem is an important candidate of postquantum cryptosystem, the proposed code-based chameleon signature scheme would be a promising alternative to the number theoretic based schemes. In addition, we also propose a method to transform the code-based chameleon hashing scheme into an ordinary signature scheme and prove its unforgeability in the random oracle model.